The Effect of Profitability and Company Size on Transfer Pricing with Tax Minimization as a Moderating Variable - Setiawan, Purnama Ariska Tri; Arfah, Ariyati; Junaid, Asriani (Invoice : Jurnal Ilmu Akuntansi, 2025)
This study aims to examine the effect of profitability and company size on transfer pricing, with tax minimization as a moderating variable, in mining industry companies listed on the Indonesia Stock Exchange (IDX). Using secondary data from annual reports of mining companies from 2021 to 2023, this research adopts a purposive sampling method to select relevant samples. The study employs descriptive statistical analysis and Partial Least Squares (PLS) for hypothesis testing. The findings reveal that profitability has a positive and significant effect on transfer pricing, indicating that more profitable companies are more likely to engage in transfer pricing practices. Similarly, company size also exerts a positive and significant influence on transfer pricing, suggesting that larger firms tend to use transfer pricing mechanisms more actively. Furthermore, tax minimization strengthens the positive relationship between profitability and transfer pricing, implying that companies with higher profitability and a focus on tax efficiency are more inclined to leverage transfer pricing strategies. Likewise, tax minimization moderates the relationship between company size and transfer pricing, reinforcing that larger firms with tax minimization objectives are more likely to engage in transfer pricing practices. These findings contribute to the understanding of corporate tax strategies and provide insights for regulators in monitoring transfer pricing activities within the mining sector.